The cervical cancer vaccine in Ireland: Well worth the wait - Mc Larnon, Eva; Murphy, Aimee (Trinity Student Medical Journal, 2010)
Cervical cancer is the third most common cancer in women and results in approximately 300,000 deaths worldwide per annum. Research has un- covered that infection with particular types of the human papilloma virus (HPV) is the strongest independent risk factor for the development of cervical carcinoma. Due to this relationship, vaccines against the foremost carcinogenic strains of the virus were developed in hopes that they would prevent the subsequent development of malignancy. Two vaccines currently exist: the quadrivalent vaccine, Gardasil and the bivalent vaccine, Cervarix. Both vaccines target the two Human Papillomavirus strains that are most commonly associated with the development of cervical cancer, types 16 and 18. The Gardasil vaccine also targets Human Papillomavirus types 6 and 11, which are commonly associated with genital warts. Five- year follow-up studies have shown both vaccines to be over 90% efficacious. There is, however, a lack of long-term data on both vaccines and more research is necessary to further evaluate their long-term outcomes on the prevention of malignancy. Currently, the major protection offered to women in Ireland against cervical cancer is that of secondary prevention via regular screening with the papanicolaou smear. A vaccine campaign is due to commence later this year, with the introduction date currently set as September 2010. It is expected that immunisation against the Human Papillomavirus in combination with regular papanicolaou smear screening will result in a reduction in the incidence of cervical cancer in Ireland. In this review, the link between cervical cancer and the Human Papillomavirus will be discussed in addition to providing support for the introduction of the Human Papillomavirus vaccines into the Irish immunisation schedule.